Endoscopic management of magnet ingestion and its adverse events in children - Radhika Chavan, MD, DNB; Vatsal Bachkaniwala, MD, DM; Varun Tadkalkar, MD, DM; Chaiti Gandhi, MD, DNB; Sanjay Rajput, MD, DM (VideoGIE, 2022)
Background and Aims: Magnet ingestion has recently increased among children. Multiple magnets can lead to serious adverse events owing to pressure necrosis of trapped bowel wall; therefore, urgent removal of the magnet is recommended. However, awareness of magnet ingestion and adverse events associated with it are lacking among the general population and some healthcare professionals. Herein, we demonstrate the adverse events associated with prolonged retention of ingested magnets and endoscopic management of ingested magnets in children. Methods: We present a case series of 3 patients with magnet ingestion. Foreign body ingestion was confirmed on fluoroscopy. After fluoroscopy, all children underwent EGD under propofol sedation in a left lateral position. A Roth net was used to remove magnets. Results: Three patients (median age 5 years), each with ingestion of 2 magnets of different shapes and sizes and with variable periods of ingestion, underwent EGD. In 2 patients, both magnets were Successfully removed. In 1 patient, 1 magnet could not be removed because it became dislodged deep in the jejunum. All 3 patients had developed magnet-related fistula (gastroduodenal: 1 patient; duodenojejunal: 2 patients). Patients with duodenojejunal fistula were managed conservatively. There was mild self-limited bleeding during magnet removal in 1 patient. There were no major adverse events related to endoscopic removal. Conclusions: Endoscopic removal of magnets is feasible and safe in children. Few patients with fistulas can be managed conservatively. There is an unmet need to increase societal awareness of magnet ingestions and adverse events associated with it.